2018
DOI: 10.1155/2018/9326820
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur and Nitrogen Fertilization as a Potential Means of Agronomic Biofortification to Improve the Content and Uptake of Microelements in Spring Wheat Grain DM

Abstract: The aim of the field experiment was to analyze the impact of various nitrogen and sulphur doses on the content and uptake of spring grains of iron, manganese, copper, and zinc. The study was conducted in southeastern Poland (2009–2011) on Cambisols (WRB 2007), in conditions of low soil sulphur content. The experiment included 4 doses of N fertilization (0, 40, 80, and 120 kg/ha) and 2 doses of S application (0 and 50 kg/ha). The analysis showed that fertilization with nitrogen and sulphur had a positive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 71 publications
(93 reference statements)
2
25
0
Order By: Relevance
“…The concentration of such microelements as Zn, Mn and Fe in plants strictly correlates with their content in the soil and its pH. As pH increases, the contents of Zn and Mn in the plant decrease [82]. In this study, soil pH varied between acidic (5.0) in galega growth and neutral (6.8) in winter wheat growth.…”
Section: Zinc Manganese and Potassium Content In Wheat Leaves And Grmentioning
confidence: 58%
“…The concentration of such microelements as Zn, Mn and Fe in plants strictly correlates with their content in the soil and its pH. As pH increases, the contents of Zn and Mn in the plant decrease [82]. In this study, soil pH varied between acidic (5.0) in galega growth and neutral (6.8) in winter wheat growth.…”
Section: Zinc Manganese and Potassium Content In Wheat Leaves And Grmentioning
confidence: 58%
“…As for the micronutrients, the current study revealed a significant decrease in Mn concentrations in the three cultivars under −S ( Table 2 ). It has been reported that Mn acquisition can be affected by S supply and S application can promote Mn uptake at the cellular level [ 45 ]. Given the close synchronization with S, it is likely that the decrease in Mn concentrations observed could be attributed to S scarcity.…”
Section: Resultsmentioning
confidence: 99%
“…The only soil factor that correlated with honey MGO was soil NO 3 − ( r = −0.88, p < 0.05) ( Figure 4 ). NO 3 − was shown to accelerate L. scoparium root growth [ 37 , 38 ] and could increase the accumulation of Fe, Mn, Zn, and Cu [ 53 ]. However, soil NO 3 − only correlated positively with plant Co ( r = 0.49, p ≤ 0.005).…”
Section: Resultsmentioning
confidence: 99%